VALIDASI METODE PENENTUAN MINYAK DAN LEMAK PADA AIR DENGAN FOURIER TRANSFORM INFRA-RED (FTIR) DI PT. KEHATILAB INDONESIA - Suyono, Hadi; Sapta Dewi, Yusriani (JURNAL TECHLINK, 2024)
This study has been conducted to validate the method of determining oil and fat in water with fourier transform infra-red (FTIR) type L1600100 spectrum two serial number 123010. This study aims to determine the method of oil and fat analysis using fourier transform infra-red (FTIR) can measure oil and fat levels up to 1 mg / l. The results obtained were compared with the acceptance requirements obtained. The results obtained were compared with the acceptance requirements set by PT Kehatilab Indonesia so that it can be used for routine analysis. Based on the experiments that have been carried out for the linearity test, the coefficient of determination (R2) value is 0.9996. The accuracy test obtained a %recovery value of 98.20% with a range value of (96.29 - 100.54)%. The precision test obtained a %RSD value of 1.48%. LoQ (Limit of Quantity) test obtained a value of 0.5 mg/l. MDL (Method Detection Limit) test obtained a value of 0.2 mg / l. The repeatability test obtained a %RSD value of 4.22% for low levels, 4.85% for medium levels and 3.01% for high levels. The reproducibility test obtained a %RSD value of 4.24% for low levels, 4.21% for medium levels and 3.71% for high levels. All test parameters have met the acceptance requirements so that the method of determining oil and fat content in water with fourier transform infra-red (FTIR) can be used for routine analysis at PT Kehatilab Indonesia.